Energy-Proportional Computing: A New Definition. - Sen, Rathijit; Wood, David A. (Computer (00189162), 2017)
A new energy-proportional computing model extends Barroso and Hölzle's original definition for fixed-resource systems to aid in the design of more efficient modern systems with reconfigurable resources that can be varied at runtime.